Herbal medicinal importance of Citrullus Lanatus mentioned in the Ahadith: a precise overview - Islam, Md. Sirajul; Samsudin, Sofiah; A.K., Azad (iMedPub LTD, 2015)
This study focuses on the herbal medicinal importance of watermelon (citrulluslanatus) mentioned in the Ahadith. Objective: The main objective of this study is integration between the Ahadith and the modern clinical reports on the herbal medicinal importance of watermelon. Methods: It has been discussed in this study followed by botanical name, the name mentioned in the Prophetic traditions, Arabic name, English name, family, part used, nature and flavor, basic substance and medicinal use. Results: The study proved that there is no contradiction between the Ahadith and modern clinical reports on the herbal medicinal importance of this fruit. Conclusion: In conclusion, we can say in the light of this study that herbal medicine and modern medicine are complementing each other to promote human’s health and comfort and always should be thankful to the Creator for His blessings.